Impact of Matrix Metalloproteinase 9 on COPD Development in Polish Patients: Genetic Polymorphism, Protein Level, and Their Relationship with Lung Function. (10th December 2018) - Gilowska, Iwona; Kasper, Łukasz; Bogacz, Katarzyna; Szczegielniak, Jan; Szymasek, Teresa; Kasper, Marta; Czerwinski, Marcin; Sładek, Krzysztof; Majorczyk, Edyta
Abstract : Chronic obstructive pulmonary disease (COPD) is characterized by a decline of lung function and symptoms such as chronic bronchitis and emphysema leading from lung tissue destruction. Increased activity of matrix metalloproteinases (MMPs) and an imbalance between MMPs and their tissue inhibitors (TIMPs) are considered as factors influencing the pathogenesis of COPD. We investigated the role of genetic polymorphism and expression level of MMP-9 and concentration of its complexes with TIMPs in the development of COPD among Polish patients. We analyzed SNP in the promoter region of MMP-9 gene (rs3918242) using PCR-RFLP method among 335 COPD patients and 309 healthy individuals. Additionally, 60 COPD patients and 61 controls were tested for copy number variants (CNV) of MMP-9 (by quantitative real-time PCR) and serum levels of MMP-9 and its complexes with TIMP1 and TIMP2 (using ELISA). All subjects were analyzed for lung function using spirometry (FEV1 % and FEV1 /FVC parameters). We observed that allele and genotype frequencies of the SNP rs3918242, as well as the number of gene copies, were similar in COPD patient and controls groups. Serum levels of MMP-9 and MMP-9/TIMP1 complex were significantly higher in COPD patients in comparison to controls groups, although independently of analyzed gene polymorphisms. Additionally, the significant inverse relationships between parameters of lung function (FEV1 % and FEV1 /FVC) and proteins level were found in ridge regression models, especially we found that FEV1 % decreased when MMP-9 level increased in controls and patients with COPD group. In conclusion, we found that COPD patients were predisposed to produce more MMP-9 and MMP-9/TIMP1 complex than healthy individuals. This phenomenon is probably associated with the disease-related lung environment but not with genetic features of the MMP-9 .